2019
DOI: 10.1159/000495982
|View full text |Cite
|
Sign up to set email alerts
|

Long-Wave Medical Infrared Thermography: A Clinical Biomarker of Inflammation in Hidradenitis Suppurativa/Acne Inversa

Abstract: Background: A more reliable classification of skin inflammation and severity of active disease results from ultrasound sonography and the new hidradenitis suppurativa/acne inversa (HS) classification system IHS4. However, an objective assessment of skin inflammation in a continuous mode is still the ultimate goal. Long-wave medical infrared thermography (MIT) may offer a blood flow and temperature differential assessment in inflammatory conditions. Objective: To evaluate the application of MIT in HS. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 35 publications
0
26
0
4
Order By: Relevance
“…Robust ex vivo models might corroborate clinical data. 197 Clearer documentation and newer diagnostic techniques, such as standardized photography, ultrasound and thermography 66,[198][199][200]…”
Section: What Are We E Xpec Ting In the Future?mentioning
confidence: 99%
“…Robust ex vivo models might corroborate clinical data. 197 Clearer documentation and newer diagnostic techniques, such as standardized photography, ultrasound and thermography 66,[198][199][200]…”
Section: What Are We E Xpec Ting In the Future?mentioning
confidence: 99%
“…MIT has assessed burn wound depth (66) and is being actively investigated as an alternative to ultrasound in the grading of HS. MIT has been correlated with qualitative changes in Doppler blood flow in HS (67) and have defined tissue margins in HS skin removal surgery (67, 68). It remains unclear whether the accuracy and reproducibility of MIT is influenced by body site, previous surgical excisions and microvascular disease from smoking and/or metabolic syndrome, which may all influence tissue blood flow (69).…”
Section: Resultsmentioning
confidence: 99%
“…MIT does not cause pain to HS patients, is relatively fast, and is highly temperature‐sensitive with adequate spatial resolution . Recently, MIT has been utilized to detect HS as it can detect the associated inflammation . First, MIT has been shown to be helpful as a supplementary assessment during surgical resection of an HS lesion after pre‐surgical MRI.…”
Section: Overview Of Current Imaging Modalities Used For Hsmentioning
confidence: 99%
“…It was demonstrated that a 1°C temperature difference between skin areas corresponded to HS inflammation. Objectively, MIT displayed healthy skin as 33°C areas whereas HS‐affected, and thus generally inflamed, areas averaged 35°C or above . However, as MIT detects differences in temperature, it can only detect inflamed HS lesions and has no utility in the detection of non‐inflamed sinus tracts or in patients with co‐localized inflammation due to another cause.…”
Section: Overview Of Current Imaging Modalities Used For Hsmentioning
confidence: 99%